HK Spaces with AD Property - Abdallah A. Hakawati (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
If H is an HK space which has AD property, then we define the matrix A(H)= (amn) as am=< em,en>H. We prove that A(H) is uniquely determined by H , and hence conclude that there is a one - to - one map between the collection of all HK spaces which have AD, and that of all matrices which are positive definite and Hermitian. Finally, we calculate A(H2|w) where W={dn} is an interpolating sequence.